2021
DOI: 10.34172/bi.2021.23634
|View full text |Cite
|
Sign up to set email alerts
|

Effect of α-pinene and thymoquinone on the differentiation of bone marrow mesenchymal stem cells into neuroprogenitor cells

Abstract: Introduction: Neurodegenerative diseases are accompanied by loss of neuronal function and integrity. Stem cell therapy is utilized to regenerate neurons to repair the damaged area. Regeneration potential of stem cells can be enhanced by using chemicals with known bioactive properties. In the current study, two bioactive compounds, α-pinene (AP) and thymoquinone (TQ) were explored for their neuronal differentiation potential of rat bone marrow mesenchymal stem cells (MSCs). Methods: MSCs were isolated, cultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 26 publications
(22 reference statements)
2
7
0
Order By: Relevance
“…There was significant upregulation of neuron and glial specific markers that is, NSE, Tau, Nestin, NefL, MAP2 , and GFAP . Similar study has been conducted previously by our group that reported the expression of astroglial marker that is, GFAP along with the neuronal markers in differentiated MSCs 25 . Some other studies also reported the expression of GFAP in differentiated neuronal cells 26 .…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…There was significant upregulation of neuron and glial specific markers that is, NSE, Tau, Nestin, NefL, MAP2 , and GFAP . Similar study has been conducted previously by our group that reported the expression of astroglial marker that is, GFAP along with the neuronal markers in differentiated MSCs 25 . Some other studies also reported the expression of GFAP in differentiated neuronal cells 26 .…”
Section: Discussionsupporting
confidence: 87%
“…However, genes of endoderm ( AFP, Sox17 , and MixL1 ) and mesoderm ( MesP1 and T Brachyury ) layers were also upregulated. At this stage, cells expressed neuronal markers representing their neuroprogenitor state, but overexpression of genes representing meso and endodermal layers simply explains the transition phenomenon from ectoderm to the other two germ layers, as reported in our previous study 25 …”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations